2023
DOI: 10.7717/peerj.14652
|View full text |Cite
|
Sign up to set email alerts
|

Mass media pressure on physical build, psychological well-being and physical-healthy profile. An explanatory model in adulthood

Abstract: Background The pressure exerted by the media on mental image, psychological well-being and the physical-dietary sphere is of vital interest in understanding human behavioral patterns at different stages of development. The present research reflects the objectives of developing an explanatory model of the associations between media pressure and physical build on psychological well-being, physical activity and the Mediterranean diet and testing the structural model using a multi-group model according to particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…It has been observed that external pressure often comes from different social networks or the media [ 15 ]. In the youth population, a very high consumption of media content has been observed [ 16 ]. There are many areas within the media that focus on taking care of body image [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that external pressure often comes from different social networks or the media [ 15 ]. In the youth population, a very high consumption of media content has been observed [ 16 ]. There are many areas within the media that focus on taking care of body image [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the youth population, a very high consumption of media content has been observed [ 16 ]. There are many areas within the media that focus on taking care of body image [ 16 ]. Research argues that the transmission of such messages in the media and on social networks can lead to body dissatisfaction in young people [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation